Réponses

  • Utilisateur Brainly
2014-04-16T16:12:05+02:00
Ex 1 :

2(x + 3) = 2x + 6
x(x - 5) = x² - 5x
- 5x(3x + 4) = - 15x² - 20x
- 2x(3x - 2) = - 6x² + 4x

Ex 2 :

12x + 9
= (3 X 4x) + (3 X 3)
= 3 (4x + 3)

4x² + x
= (4x X x) + (x X 1)
= x(4x + 1)

3t² + t³
= (3 X t²) + (t² X t)
= t²(3 + t)

Ex 3 :

(2x - 1)(3 - x)
= (2 X 5 - 1)(3 - 5)
= 9 X (- 2)
= - 18

3x² - 2x + 1
= (3 X (- 3))² - 2 X (- 3) + 1
= (- 9)² + 6 + 1
= 88

Ex 4 :

4x² - 6x + 8 - 3x² + 9x - 2
= 4x² - 3x² - 6x + 9x + 8 - 2
= x² + 3x + 6

Ex 5 :

5x² - (3x + 7x) - 4 + (3x² - 8x) + 9
= 5x² - 3x - 7x - 4 + 3x² - 8x + 9
= 5x² + 3x² - 3x - 7x - 8x - 4 + 9
= 8x² - 18x + 5

Ex 6 :

2x(x - 3) - 5 (2x + 1) + (3x - 4)
2x² - 6x - 10x - 5 + 3x - 4
2x² - 6x - 10x + 3x - 5 - 4
2x² - 13x - 9

Bonne continuation! :)